Revisiting the relationship between resistance training dose and strength gains: what is the real role of volume? - Kassiano, W.; Costa, B.; de Lima-Júnior, D.; Gantois, P.; de Souza Fonseca, F.; de Sousa Fortes, L. (Journal of Trainology, 2021)
Resistance training (RT) volume is considered a critical variable to induce neuromuscular adaptations (i.e., increased muscular strength). However, emerging findings have allowed us to revisit the role of volume in strength gains. Objectives: In the present study, we seek to present these emerging findings to discuss the role of RT volume in one-repetition maximum (1RM), isometric, and isokinetic strength gains. In addition, we propose alternative ways to test whether or not volume plays a determining role in strength adaptation. Design & methods: We reviewed the literature on RT volume and strength. In addition, we examined the RT literature to provide alternative ways to investigate the effect of volume on changes in strength. Results/conclusions: From the recent findings, we argue that an increase in strength can be achieved through a refined interaction between skill enhancement, regular use of high loads, and neuromuscular fatigue management; these points can be obtained from different RT volumes. From an inquiring point of view, we suggest that future investigations that aim to verify the effects of volume on muscular strength may consider the inclusion of high load sessions (80-100% of 1RM), periodically (e.g., every three or four weeks), in both low and high-volume groups, as well as considering the inclusion of different strength measures (e.g., isokinetic and isometric). We believe that this will help to clarify the nature of the relationship between RT volume and strength adaptations.